The role of social studies teachers in enhancing the concepts of media education among students of the higher basic stage in Jordan during the Covid- 19 pandemic - Hassan, Salsabil Adeeb; Irsheed, Mamoun Ahmed; Obeidat, Ghaith Hassan (Journal of Educational and Psychological Sciences, 2021)
The study aimed to identify the role of social studies teachers in enhancing the concepts of media education among students of the higher basic stage in Jordan during the Covid- 19 pandemic. The study population consisted of all social studies teachers for the higher basic stage in the capital Amman, Irbid Governorate, and Salt Governorate. The sample consisted of (415) male and female teachers, who were chosen by the random stratified method. The questionnaire was used as a study tool. The results showed that the level of social studies teachers ’enhancement of media education concepts among upper basic stage students in Jordan during the Covid- 19 pandemic was high, with the mean totaling (4.25). The results also indicated that there are no statistically significant differences between the social studies teachers ’response averages to the level of enhancing media education concepts among students of the higher basic stage in Jordan during the Covid- 19 pandemic due to the variables of gender, academic qualification, and number of years of experience. The study recommended the necessity of emphasizing the role of teachers in promoting the concepts of media education among students, increasing their awareness of media issues and how to deal with them, and protecting them from forgery and distortion in light of the media and cultural openness.